Oxidative status and lymphocyte DNA damage in patients with acute pancreatitis and its relationship with severity of acute pancreatitis - Dur, Ali; Kocaman, Orhan; Koçyiğit, Abdurrahim; Türkdoğan, Kenan Ahmet; Sönmez, Ertan; Keskin, Sıddıka; Yiğit, Mehmet; Gülen, Bedia; Kılıç, Elif; Uysal, Ömer (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: Acute pancreatitis (AP) is a life-threatening disease with a rising incidence. The aim of this study was to investigate the association between oxidative status, lymphocyte deoxyribonucleic acid (DNA) damage, and acute pancreatitis. Materials and Methods: A total of 45 patients with AP and 35 healthy controls were included in the study. We assessed pancreatic enzymes, oxidative stress, and lymphocyte DNA damage. The severity of AP disease was determined by the Harmless Acute Pancreatitis Score (HAPS) and Balthazar scoring systems. Results: In AP patients, lymphocyte DNA damage was significantly higher than in controls [49.84±25.48 arbitrary units (AU) vs. 28.80±13.98 AU, p<0.001]. The plasma total oxidative status (TOS) and oxidative stress index (OSI) were higher in patients than in healthy controls (10.36±5.54 vs. 8.47±2.66, p<0.05; 0.64±0.35 vs. 0.45±0.13 AU, p<0.001, respectively). The plasma total antioxidant status level in patients was lower than in healthy controls (1.66±0.19 vs. 1.86±0.18, p<0.001). Lymphocyte DNA damage was correlated with TOS, OSI, and HAPS and Balthazar scores. Conclusion: This study shows that patients with AP have higher lymphocyte DNA damage and more deteriorated oxidative status than healthy controls.